Factors Influencing Glucoraphanin and Sulforaphane Formation in Brassica Plants: A Review - Zhen-xin GU; Qiang-hui GUO; Ying-juan GU (Journal of Integrative Agriculture, 2012)
Sulforaphane is a type of sulfur-containing isothiocyanates hydrolyzed from glucosinolates by myrosinase found in Brassica plants. Sulforaphane is a naturally occurring inducer of phase II enzymes in human and animal bodies to detoxify cancer-causing chemicals. Glucoraphanin is the precursor of sulforaphane and its content is greatly influenced by plant species and genotype, plant organs, pre-harvest factors, and post-harvest processing, thus sulforaphane formation is also directly influenced. Here, we review the formation mechanism of sulforaphane and the factors influencing sulforaphane formation. In the end, the future directions are also discussed.